Application and Development of Bio-sand Filtration Technology for Processing Drinking Water in Rural Areas - ZHANG Kexuan; LI Jie; XIAO Juqiang (Renmin Zhujiang)
It has been a focus for researchers to study how to ensure the safety of drinking water in rural areas.Bio-sand filtration (BSF) technology has advantages including convenient construction,low water production costs,low energy consumption,and stable and reliable operation,and thus it is more suitable for promotion in rural areas than that in cities.Considering the water shortage and drinking water safety issues,this paper introduces the removal effects of BSF on pollutants such as turbidity,organic pollution,nitrogen and phosphorus,bacteria,and metals,and the advantages and disadvantages of BSF are compared.Moreover,the future application prospects of BSF technology are discussed.